2020
DOI: 10.1042/bcj20200392
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary hemochromatosis promotes colitis and colon cancer and causes bacterial dysbiosis in mice

Abstract: Hereditary hemochromatosis (HH), an iron-overload disease, is a prevalent genetic disorder. As excess iron causes multitude of metabolic disturbances, we postulated that iron overload in HH disrupts colonic homeostasis and colon-microbiome interaction and exacerbates the development and progression of colonic inflammation and colon cancer. To test this hypothesis, we examined the progression and severity of colitis and colon cancer in a mouse model of HH (Hfe-/-), and evaluated the potential contributing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…In this way, influx of extracellular citrate could release not only mitochondria from excess citrate synthesis, reduce ROS production (therefore increase resistance to chemotherapy) but also allow the use of other metabolic pathways like PPP in the most beneficial way for cancer cells. It is therefore not surprising that chronic exposure to excess iron as occurs in the genetic iron-overload disease hemochromatosis transforms normal cells into cells with a tumor phenotype (Gnanaprakasam et al, 2013;Bhutia et al, 2020) and also increases the risk of cancer, particularly liver cancer (Grosse et al, 2018) and colon cancer (Sivaprakasam et al, 2020).…”
Section: Citrate Metabolism In Cytoplasmmentioning
confidence: 99%
“…In this way, influx of extracellular citrate could release not only mitochondria from excess citrate synthesis, reduce ROS production (therefore increase resistance to chemotherapy) but also allow the use of other metabolic pathways like PPP in the most beneficial way for cancer cells. It is therefore not surprising that chronic exposure to excess iron as occurs in the genetic iron-overload disease hemochromatosis transforms normal cells into cells with a tumor phenotype (Gnanaprakasam et al, 2013;Bhutia et al, 2020) and also increases the risk of cancer, particularly liver cancer (Grosse et al, 2018) and colon cancer (Sivaprakasam et al, 2020).…”
Section: Citrate Metabolism In Cytoplasmmentioning
confidence: 99%
“…The role of the gut microbiome in different type of diseases has been discussed in many previous studies. At present, intestinal dysbacteriosis is considered an important factor during the development of diseases (2,4,(19)(20)(21). The therapeutic influences of AT-I have been discussed in numerous studies; however, reports on the effect of AT-I on the gut microbiome are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the number of certain beneficial or harmful bacteria can disrupt the balance of intestinal flora, leading to the possibility of colon cancer. By analyzing the difference in bacterial composition in the stool of healthy people and colorectal cancer patients, it was found that a variety of beneficial bacteria and bacterial diversity in the stool of colorectal cancer patients decreased, and the proportion of harmful bacteria increased significantly (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…This is evident from the increased incidence of liver cancer in patients with hemochromatosis, a genetic disease of iron overload [ 71 ]. In fact, the connection between excess iron and cancer could go beyond the liver as our recent studies have demonstrated the connection between hemochromatosis and colon cancer in preclinical mouse models [ 72 ]. The publicly available TCGA (the cancer genome atlas) database indicates that SLC13A5 is also up-regulated several fold in pancreatic adenocarcinoma and that the expression levels have a negative correlation with patient survival.…”
Section: Biology Of Nact In Liver and Its Connection To Metabolic Patmentioning
confidence: 99%